Τhe Homeric ἵστωρ and oath-taking - Basile, Gastón Javier (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2018)
The paper reassesses the role and function of the Iliadic ἵστωρ (Il XVIII 490-508; XXIII 448- 508) by focusing on previously overlooked narrative and linguistic details and drawing parallelisms between both scenes. The paper argues that the most fundamental cognitive operation performed by the ἵστωρ entails confining to memory and recording the ‘particulars’ of words spoken at a given time and in a specific context. This social function is closely connected to the centrality of memory in the early Greek world, oath-taking and the psychodynamics of orality, as evidenced by invocations to the Gods in the Homeric poems as well as later uses of the word in the context of oaths and solemn vows.